If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + -6 = 9 Reorder the terms: -6 + 1x = 9 Solving -6 + 1x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 1x = 9 + 6 Combine like terms: -6 + 6 = 0 0 + 1x = 9 + 6 1x = 9 + 6 Combine like terms: 9 + 6 = 15 1x = 15 Divide each side by '1'. x = 15 Simplifying x = 15
| (.1x-33)+(.4x-40)=180 | | x=2x-132 | | (-3x+79)= | | 7st+4t(t+s+4)-9= | | x+7-4=-15 | | 300=-(420*600*1500)-(-1c*600*1500)-(1000*600*1500) | | -14+3x=11 | | 3u-8=-20 | | -10y=x+21 | | 4y-5+y+19=5y+20-2y | | 10=5+5y | | 2x=x-46*x-86 | | .1x-33+.4x-40=180 | | 1x-3=9 | | -6=5u+4 | | n+20=100 | | -6=1/2x-4 | | 7(5+6x)=203 | | 10-4(6-x)+5= | | -6=1/2x4 | | 6000=3x/2(2x) | | 2x+25+65=180 | | 8(y-6)=7(y+2) | | -21.8-g=9.5 | | 2x+3x-x= | | 2w+2=16 | | -12+n=-36 | | 5+3n-4=9n+7-7n | | 6+5x=(x-3)-3(x-1) | | y=-x^2+500x | | 2x+2-3=5 | | f(x)=6x-17 |